(untitled) (Research, Society and Development, 2022)
Aim: The aim of this retrospective study was to evaluate the post-surgical results of autotransplanted teeth, considering the pulp survival rate and periodontal healing. Methodology: Records of 43 patients with 50 autotransplanted teeth were analysed. Demographic, clinical and radiographic data were verified. The time between autotransplantation surgery and the date of endodontic access was considered to assess the pulp survival rate. Periodontal healing was observed through gingival morphology and the presence of root resorption. Pulp survival was verified and the influence of Nolla stage on the survival rate was analysed. Results: The pulp survival rate was 72%, and the stage of root development influenced the survival rate in autotransplanted teeth (p = 0.001). The pulp survival rate in autotransplanted teeth in Nolla stages 6 and 7 was 100%; the pulp survival rate for teeth in stages 8 and 9 was 90% and 75%, respectively. Regarding periodontal analysis, no tooth was observed in the presence of periodontal pockets and mobility above grade I. Replacement resorption was diagnosed in 20% and external inflammatory resorption in 4%. Conclusions: Dental autotransplantation was a safe treatment, showing satisfactory results. The pulp survival rate was considered high, especially in teeth with incomplete rhizogenesis.